Collective modes and superfluidity of a two-dimensional ultracold Bose gas - Vijay Pal Singh; Ludwig Mathey (Physical Review Research, 2021)
The collective modes of a quantum liquid shape and impact its properties profoundly, including its emergent phenomena such as superfluidity. Here we present how a two-dimensional Bose gas responds to a moving lattice potential. In particular, we discuss how the induced heating rate depends on the interaction strength and the temperature. This study is motivated by the recent measurements of Sobirey et al. [arXiv:2005.07607], for which we provide a satisfying understanding. Going beyond the existing measurements, we demonstrate that this probing method allows us to identify two sound modes in quantum liquids. We show that the two sound modes undergo hybridization as a function of interaction strength, which we propose to detect experimentally. This gives insight into the two regimes of Bose gases, defined via the hierarchy of sound modes.